A proposed remedy to the inequitable representation of nursing in the Australian National Disability Insurance Scheme. Issue 2 (April 2023) - Cashin, Andrew; Pracilio, Amy; Wilson, Nathan J.
Abstract: Background: The National Disability Insurance Scheme (NDIS) is the policy framework that has enabled a revolution in disability related support funding in Australia. The framework includes assumptions related to which professionals are eligible to provide supports under the scheme and the relative fiscal value of these supports. Aim: To identify how nurses are represented in the NDIS as laid out in relevant policy documents to identify assumptions embedded related to the pricing of nursing supports. Methods: Policy analysis of the representation of nursing in the NDIS as presented in the NDIS documentation related to provider status within the Registered and Enrolled Nurse scopes of practice and pricing arrangements. Findings: Provider inequity is identified to exist as Registered Nurses, including Nurse Practitioners, are for the most part represented in a structure shared with Disability Support Workers and Psychosocial Recovery Coaches as opposed to other comparable professionals. Price limits are lower for services provided by nurses than other comparable, or less qualified, providers. Discussion: An alternative representation and pricing arrangement is proposed with associated costings that would solve the issue of provider inequity and potentially increase access to nursing supports for people with disability in Australia. Conclusion: The current representation of nursing in the NDIS is limiting the availability of suitably qualified professionals to NDIS participants and restricting the market mechanism aimed for in the NDIS.